The Relationship between Job Insecurity, Work distress and Anxiety with Hypertension in Fishing Equipment Manufacturing Worker - Caroline Anggraeni; Ahmad Fuady; Suryo Wibowo; Dewi Sumaryani Soemarko; Marsen Isbayuputra (ILUNI MKK FKUI and PRODI MKK FKUI, 2025)
Background: Hypertension is one of the main risk factors for cardiovascular disease and can be influenced by psychosocial factors such as job insecurity, work distress, and anxiety. The objective of this study to analyze the impact of job insecurity, work distress, and anxiety on the incidence of hypertension among employees. Explore the mediating role of distress and anxiety in the relationship between job insecurity and hypertension.Method: There was a cross-sectional design, encompassing a population of employees from a fishing equipment manufacturing company. Consecutive sampling was utilized to select study participants, and data was collected via COPSOQ III questionnaires for assessed job insecurity, the 4DSQ instrument for assesses work distress and anxiety, and measuring blood pressure. The collected data underwent logistic regression analysis for mediating role of work distress and anxiety in the relationship between job insecurity and hypertensionResult: In the bivariate analysis, the probability of hypertension is significantly 4.05 times higher in workers experiencing moderate distress than low distress. In the multivariate analysis, after adjusting for dependent variables, ikelihood of hypertension is 3.88 times higher in workers experiencing moderate distress compared to those with low distress.Conclusion: There is a correlation between work distress and hypertension among workers in a fishing equipment manufacturing company. Work distress and anxiety do not serve as mediators in the relationship between job insecurity and hypertension among workers. Recommendations for this company is implementation of distress management programs such as training in relaxation techniques, or counseling to reduce worker distress.